2011
DOI: 10.1517/13543776.2011.545347
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor as an anticancer drug and new treatment methods following the discovery of its receptors: a patent perspective

Abstract: Background-Traditional forms of cancer therapy, which includes chemotherapy, have largely been overhauled due to the significant degree of toxicity they pose to normal, otherwise healthy tissue. It is hoped that use of biological agents, most of which are endogenously present in the body, will lead to safer treatment outcomes, without sacrificing efficacy.Objective-The finding that PEDF, a naturally-occurring protein, was a potent angiogenesis inhibitor became the basis for studying the role of PEDF in tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In this regard, PEDF may link the molecular networks of angiogenesis and lipid metabolism. The therapeutic potential of PEDF, predominantly as anticancer drug, is under investigation [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, PEDF may link the molecular networks of angiogenesis and lipid metabolism. The therapeutic potential of PEDF, predominantly as anticancer drug, is under investigation [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that PEDF level declines with age, and suggested that this decline may play a key role in the development of angiogenic-related pathologies (18). Moreover, it was shown that decrease in PEDF expression is one of the mechanisms that promote tumor growth (19), suggesting PEDF as an anticancer therapy (20,21). We have recently characterized the expression and regulation of PEDF in human and rodent premenopausal endometrium, indicating that PEDF is dynamically expressed in mice endometrium throughout the estrous cycle, in reciprocity to VEGF, and that the balance between the two is regulated by estrogen and progestrone (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently characterized the expression and regulation of PEDF in human and rodent premenopausal endometrium, indicating that PEDF is dynamically expressed in mice endometrium throughout the estrous cycle, in reciprocity to VEGF, and that the balance between the two is regulated by estrogen and progestrone (22,23). PEDF is a secreted glycoprotein that promotes a variety of activities upon binding to various receptors (20). In our previous studies, we showed that endometrial cells express Patatin-like phospholipase domain-containing protein 2 (PNPLA2; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies conducted in endothelial cells showed that survival and apoptotic cascades occur simultaneously within a single cell; the switch between the processes depends on changes in the balance between PEDF and VEGF (Pollina et al 2008). However, detailed studies are still required to fully understand the mechanism behind these networks (Manalo et al 2011).…”
Section: Pedf and Vascular Endothelial Growth Factormentioning
confidence: 99%
“…To achieve a proper angiogenesis, an accurate balance between proand anti-angiogenic factors must be maintained (Manalo et al 2011); any failure in angiogenesis can lead to diverse pathologies.…”
Section: Angiogenesis In the Reproductive Systemmentioning
confidence: 99%